A comprehensive splicing characterization of COL4A5 mutations and prognostic significance in a single cohort with X-linked alport syndrome - Li, Haomiao; Zhang, Shengnan; Zhou, Wei; Wang, Chunli; Zhu, Chunhua; Zhao, Sanlong; Zhao, Fei; Jia, Zhanjun; Zhang, Aihua; Zheng, Bixia; Ding, Guixia (Frontiers in Genetics, 2025)
IntroductionX-linked Alport syndrome (XLAS), caused by mutations in the COL4A5 gene, is an X-linked hereditary disease typically characterized by renal failure, hearing loss, and ocular abnormalities. It is a leading hereditary cause of end-stage renal disease (ESRD) worldwide. Studies on the genotype-phenotype correlation in Alport syndrome suggest that splicing mutations result in more severe clinical phenotypes than missense mutations. Determining whether COL4A5 mutations lead to aberrant mRNA splicing is critical for diagnosis and prognosis.MethodsThis study retrospectively reviewed pediatric XLAS patients with COL4A5 gene mutations from a single-center cohort, summarizing and analyzing their clinical features. Minigene assay was employed to evaluate the mRNA splicing functionality of 26 single-nucleotide variants (SNVs), both intronic and exonic, identified in XLAS patients. Bioinformatics tools were used to evaluate the accuracy and sensitivity of splicing mutation prediction. Additionally, linear mixed models were applied to analyze the relationship between mutation types and prognosis in patients’ estimated glomerular filtration rate (eGFR), exploring genotype-phenotype correlations.ResultsIn this cohort, we screened 41 XLAS pediatric patients, including 32 with confirmed XLAS and nine suspected XLAS. The cohort included 21 males (51.2%) and 20 females (48.8%), with a median age at onset of 4.42 years. Among the patients, 22 presented with both hematuria and proteinuria, while 18 exhibited hematuria alone. Notably, only one patient had isolated proteinuria. Regarding mRNA splicing, among the 26 intronic and exonic SNVs, 10 mutations (38.5%) were found to cause aberrant mRNA splicing, as demonstrated by the minigene assay. Sensitivity and specificity assessments of bioinformatics tools revealed that ESE Finder demonstrated higher sensitivity, while RNA Splicer exhibited greater specificity. Furthermore, These splicing abnormalities were closely associated with a faster decline in eGFR.ConclusionThis study demonstrates that 38.5% of SNVs in the COL4A5 gene result in aberrant mRNA splicing, which is closely linked to renal function decline in XLAS. Splicing mutations are correlated with more rapid renal progression, highlighting the importance of determining the splicing effects of SNVs during genetic screening for XLAS.